How Reading Habit Support Students Self Regulated (SRL) in Literal Reading Subject at the 1st Semester in Academic Year 2022/2023 Universitas Panca Sakti Bekasi - Rusmiati, Yanti; Agustin, Iswandini (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In this day reading habit was low performance especially in the Z generation who was born in the late 1990s and early 2000s. They didn’t familiar with newspaper or magazine but they look for the information by internet. So, this study aim to find out “How Reading Habit can Support Students Self Regulated in Literal Reading Subject.” This research used descriptive qualitative Methods. Creswell (2012, p.274) explained the purposes of descriptive method is to find the detailed explanation and description about the object of the research systematically. This research was conducted at the first semester of Universitas Panca Sakti in Bekasi. The subjects of this research were fifty six students at the first semester on  literal reading class. The data collection get by two instruments namely interviews and questionnaire. This finding revealed during learning took place; the student who has reading habit can easier to do all Reading Test than the student hasn’t reading habit. They agreed that the students need to have their own learning skills during learning. The result proves that how reading habit can support the students’ self regulated learning especially in literal reading subject.